Evaluating the impact of social networks in rural innovation systems: An overview - Matuschke, Ira (International Food Policy Research Institute, 2008)
In light of an increasing focus on new demand-driven extension approaches that aim at accelerating the adoption of innovative technologies by smallholder farmers in developing countries, greater analysis is needed of the role of rural social networks and their impact on technology adoption. This paper contributes to this topic by reviewing selected studies on rural social networks and by outlining a research approach that combines social network analysis with econometric estimation techniques in one coherent framework to strengthen the study of technology adoption by smallholders. If applied, such a framework could help establish which network characteristics have the greatest impact on technology uptake, thereby lending support to and improving the design of new extension approaches.